Polysaccharide-based nanocomposites for biomedical applications: a critical review. Issue 10 (26th July 2022) - Shokrani, Hanieh; Shokrani, Amirhossein; Sajadi, S. Mohammad; Khodadadi Yazdi, Mohsen; Seidi, Farzad; Jouyandeh, Maryam; Zarrintaj, Payam; Kar, Saptarshi; Kim, Seok-Jhin; Kuang, Tairong; Rabiee, Navid; Hejna, Alexander; et al.
Abstract : Polysaccharides (PSA) have taken specific position among biomaterials for advanced applications in medicine. Abstract : Polysaccharides (PSA) have taken specific position among biomaterials for advanced applications in medicine. Nevertheless, poor mechanical properties are known as the main drawback of PSA, which highlights the need for PSA modification. Nanocomposites PSA (NPSA) are a class of biomaterials widely used as biomedical platforms, but despite their importance and worldwide use, they have not been reviewed. Herein, we critically reviewed the application of NPSA by categorizing them into generic and advanced application realms. First, the application of NPSA as drug and gene delivery systems, along with their role in the field as an antibacterial platform and hemostasis agent is discussed. Then, applications of NPSA for skin, bone, nerve, and cartilage tissue engineering are highlighted, followed by cell encapsulation and more critically cancer diagnosis and treatment potentials. In particular, three features of investigations are devoted to cancer therapy, i.e., radiotherapy, immunotherapy, and photothermal therapy, are comprehensively reviewed and discussed. Since this field is at an early stage of maturity, some other aspects such as bioimaging and biosensing are reviewed in order to give an idea of potential applications of NPSA for future developments, providing support for clinical applications. It is well-documented that using nanoparticles/nanomaterials above a critical concentration brings about concerns of toxicity; thus, their effect on cellular interactions would become critical. We compared nanoparticles used in the fabrication of NPSA in terms of toxicity mechanism to shed more light on future challenging aspects of NPSA development. Indeed, the neutralization mechanisms underlying the cytotoxicity of nanomaterials, which are expected to be induced by PSA introduction, should be taken into account for future investigations.